2008
DOI: 10.1111/j.1365-2702.2007.02129.x
|View full text |Cite
|
Sign up to set email alerts
|

Workforce profile, organisation structure and role responsibility for ventilation and weaning practices in Australia and New Zealand intensive care units

Abstract: The results of this survey suggest, within the ANZ context, nurses participate actively in ventilation and weaning decisions. In addition, the results support an association between the education profile and skill-mix of nurses and the level of collaborative practice in ICU. Relevance to clinical practice. Mechanical ventilation may result in significant complications if not applied appropriately. Collaborative practice that encourages nursing input into decision-making may improve patient outcomes and reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 43 publications
2
55
1
1
Order By: Relevance
“…Most reviews of weaning from mechanical ventilation have examined only quantitative data [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Range of health care professionals [25][26][27][28][29][30][31][32][33][34][35] Patients only [36][37][38][39][40][41][42][43][44][45] Physicians only (intensivists or anesthetists working in intensive care units) [46][47][48][49] Patients' family members 50,51 Patients and nurses Participant interviews and observation 12,13,27,28,[31][32][33]40<...>…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reviews of weaning from mechanical ventilation have examined only quantitative data [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Range of health care professionals [25][26][27][28][29][30][31][32][33][34][35] Patients only [36][37][38][39][40][41][42][43][44][45] Physicians only (intensivists or anesthetists working in intensive care units) [46][47][48][49] Patients' family members 50,51 Patients and nurses Participant interviews and observation 12,13,27,28,[31][32][33]40<...>…”
Section: Discussionmentioning
confidence: 99%
“…We identified only 1 study of weaning in children, so our findings primarily relate to weaning of adult ICU patients. Studies were divided between those that identified factors important to individualized care and experience and those that investigated methods of standardizing care, such as objective parameters 10 Clochesy et al, 11 and Rose et al 22 were excluded from the thematic grid. These studies were surveys that incorporated comments from open-ended questions that were not developed into themes or categories.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, weaning management in the current Australian study involved unlimited assessment of weaning and extubation readiness performed by experienced and relatively autonomous critical care nurses using a 1:1 nurseto-patient ratio, supported by 24-h house medical staff and twice-daily rounds by intensivists. These organisational features are common to Australian ICUs in which ICU nurses commonly titrate ventilation and manage respiratory therapy according to physician-set physiologic targets [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The survey instrument was a previously validated questionnaire used to describe nursing roles and responsibilities for mechanical ventilation in adult ICUs in Australia and New Zealand 19 and 8 European countries, including the United Kingdom. 20 Wording was adapted and the questionnaire was validated for the UK pediatric setting by using a panel of 4 interprofessional pediatric experts who assessed clinical sensibility as recommended by Burns and colleagues.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…[14][15][16][17][18] Similar components of complex clinical interventions that affect outcomes of weaning protocol trials may exist in adult ICUs and PICUs. A recent international survey on clinicians' roles and responsibilities for mechanical ventilation and weaning in adult ICUs 19 showed that nurse to patient ratios other than 1 to 1 resulted in a reduced likelihood of nurses adjusting ventilator settings and determining extubation readiness and weaning failure. The survey also showed that use of weaning protocols increased collaborative decision making.…”
mentioning
confidence: 99%